PELATIHAN PENERAPAN MARKETING 4.0 PADA PERKUMPULAN OLAHRAGA KEBUGARAN INDONESIA ORKI TANGERANG SELATAN - Ivantan; Aris Ariyanto2; Ade Yusuf (Abdi Jurnal Publikasi, 2025)
Utilization of digital media such as social media, websites, or other online promotional platforms can be used to expand an organization's community coverage and expand its marketing network. Digital marketing is a marketing strategy that uses digital channels to reach consumers, build brand awareness, and increase sales conversions. The aim of this Community Service is to provide ORKI community members with the skills to become entrepreneurs through digital business and be able to carry out digital marketing strategies. The methods applied are lectures, demonstrations, documentation, sharing, questions and answers, discussions and practice creating marketing content. The results obtained were that the